Catalytic Activity of a Composition Based on Strontium Bismuthate and Bismuth Carbonate at the Exposure to the Light of the Visible Range - K. S. Makarevich; A. V. Zaitsev; O. I. Kaminsky; E. A. Kirichenko; I. A. Astapov (International Journal of Chemical Engineering)
This paper presents the results pertaining to studying the properties of the photocatalytically active composition of strontium bismuthate SrBi2.70O5.05, SrBi2.90O5.35, and SrBi3.25O5.88 and bismuth carbonate (BiO)2CO3 in molar ratios 1/0.67, 1/0.56, and 1/0.37, respectively. These compositions are obtained through pyrolytic synthesis from organic precursor complexes of strontium and bismuth with sorbitol. It has been established that the synthesised powder materials absorb the light of the visible range up to 500 nm owing to the presence of a narrow-gap semiconductor strontium bismuthate. The presence of a wide-band semiconductor (BiO)2CO3 ensures an effective separation of electron-hole pairs. The diffuse reflection spectra (DRS) of compositions differ from the analogous spectra of a mechanical mixture of these semiconductor phases with the same composition, which allows one to assume the heterostructural structure of the semiconductor system. The same heterostructure is confirmed by the results of mapping. Catalytic particles that are synthesised at a temperature of 500°C containing 27 mass% (BiO)2CO3 (corresponding to SrBi2.9O5.35/(BiO)2CO3 = 1/0.56) have the greatest activity with respect to the photodecomposition of methylene blue (MB). The possibility of controlling the optical properties and photocatalytic activity of the composition is depicted due to the joint formation of the strontium bismuthate phase and the bismuth carbonate phase.